DESIGN AND RESEARCH OF THE BROKEN BELT PROTECTOR WITH BIDIRECTIONAL AND ARC SHAPED CATCHING SCHEME FOR CONVEYER BELT - WANG ChunHua; AN Da; QIU LiPeng (Jixie qiangdu)
In order to realize the protection of broken conveyer belt with different moving direction, the scheme of broken belt protector with bidirectional and arc shaped catching scheme was proposed, and the main parameters were designed taking the GX1000 type conveyer belt as application example. The virtual prototype simulation of the broken belt protector catching process was done, and the velocity characteristic of main components was obtained. The model prototype with 1/2 structure size of the prototype machine was manufactured, and the test of catching process and the catching force were carried out. And the catching force parameters of prototype machine were derived based on small-scale model similarity theory. Consequently, the virtual and model prototype of broken conveyer belt protector with bidirectional and arc shaped catching scheme can carry out catching motion by different directions acorrding to the direction of broken belt motion, and wedge-shaped space for catching is formed and catching brake is finished. The broken belt protector single machine can realizes bidirectional catching. The limit catching force of prototype machine is higher than 56.4 kN, and the limit catching force is higher than theoretical cutting force which is 23.15 kN, and the demand of catching brake safely is met.